Biogas‐based denitrification in a biotrickling filter: Influence of nitrate concentration and hydrogen sulfide. Issue 3 (26th September 2016) - López, Juan C.; Porca, Estefanía; Collins, Gavin; Pérez, Rebeca; Rodríguez‐Alija, Alberto; Muñoz, Raúl; Quijano, Guillermo
ABSTRACT: The feasibility of NO3 − removal by the synergistic action of a prevailing denitrifying anoxic methane oxidising (DAMO), and nitrate‐reducing and sulfide‐oxidising bacterial (NR‐SOB) consortium, using CH4 and H2 S from biogas as electron donors in a biotrickling filter was investigated. The influence of NO3 − concentration on N2 O production during this process was also evaluated. The results showed that NO3 − was removed at rates up to 2.8 g mreactor −3 h −1 using CH4 as electron donor. N2 O production rates correlated with NO3 − concentration in the liquid phase, with a 10‐fold increase in N2 O production as NO3 − concentration increased from 50 to 200 g m −3 . The use of H2 S as co‐electron donor resulted in a 13‐fold increase in NO3 − removal rates (∼18 gNO3 − m −3 h −1 ) and complete denitrification under steady‐state conditions, which was supported by higher abundances of narG, nirK, and nosZ denitrifying genes. Although the relative abundance of the DAMO population in the consortium was reduced from 60% to 13% after H2 S addition, CH4 removals were not compromised and H2 S removal efficiencies of 100% were achieved. This study confirmed (i) the feasibility of co‐oxidising CH4 and H2 S with denitrification, as well as (ii) the critical need to control NO3 − concentration to minimize N2 O production by anoxic denitrifiers. Biotechnol. Bioeng. 2017;114: 665–673. © 2016 Wiley Periodicals, Inc. Abstract : A novel strategy for nitrogen removal combining simultaneously anoxic CH4 and H2 S oxidations with denitrification by DAMO and NR‐SOB, respectively, was developed in this study. Here, the authors have confirmed not only the potential use of biogas for this purpose, but also the urgent need to control N2 O production by adjusting NO3 − concentration along the process.